Faktor yang Berhubungan dengan Terinfiltrasinya Areola dan Papilla pada Karsinoma Payudara Operabel - YUSUF HERIADY; DIMYATI ACHMAD (National Cancer Center - Dharmais Cancer Hospital, 2014)
Mastectomy is one of the most frequent surgery performed for operable breast cancer and included resection of the nipple-areola complex (NAC). The risk of local recurrence behind the nipple areolar complex (NAC) is the main limitating of the nipple-sparing mastectomy (NSM) procedure. The aim of this study is to investigate the incidence and to determine associated risk factors with cancer infiltration to nipple-areola complex (NAC) in operable breast cancer patients. This is an observational analytic, cross sectional study using retrospective medical record of patients with mastectomy, at Soedarso Hospital Pontianak from 2006 to 2013. Results: In a period of 7 year, we included 310 patients, the mean age is 47,3 years (24-78 years). The NAC involvements 30,6%. In bivariate analysis showed that age, tumor size, tumor stage, lymh node status, lymvovascular invasion and tumor distance are associated with NAC involvement. In the multivariate analysis showed that only lymh node status (p = 0,001; prevalence odds ratio [POR], 1.52; 95% confidence interval [CI], 1.18?1.95), tumor distance (p<0.001; POR, 0.47; CI, 0.36?0.61) and tumor size (p = 0.012; POR, 2.05; CI, 1.17?3.60) are the only variables that remain significant predictors of NAC involvement. In the logistic regression analysis showed that high risks of NAC involvement are tumor distance >1?2 cm with T2 and lymph node status > 4 or with T3 and lymph node status negative or positive> 1; tumor distance >2?3 cm with T3 and lymph node status > 4. Conclusions: NAC involvement is 30,6%. Predictor factors of NAC involvement are lymh node status, tumor distance and tumor size. High risks of NAC involvement are tumor distance >1?2 cm with T2 and lymph node status > 4 or with T3 and lymph node status negative or positive> 1; tumor distance >2?3 cm with T3 and lymph node status > 4.